Making Dual Procurement and Supply Chain Operations: Cases in the Indonesian Higher Education - Ali Hapzi; Agus Sunarya Sulaeman; Budi Waluyo (International Journal of Supply Chain Management, 2019)
A high performing procurement and supply chain function is vital to the success of running a safe, productive and efficient educational organisation, and can make a significant contribution to both financial and operational performance Higher education institutions in Indonesia have experienced significant changes since the introduction of the semi-autonomous agency model. In the context of procurement, these agencies adopt both Government Procurement Procedure issued by the central government for all government institutions and Special Procurement Procedure prepared by the agency. Consequently, the agencies have to implement two different procurement procedures in accordance with each procedure. This study deeply looks at the implementation of the dual procurement procedures at a micro level in the context of gentrification. This research focuses on examining the use of dual procurement procedures in supporting through an exploration of the experiences of higher education in Indonesia. A central feature of procurement in the Indonesian higher education is unnecessary dual procedures. Higher education institutions have experienced many constraints in developing and implementing dual procurement procedures. The internal factors include risk, human resources, quality, and organizational structure, while external factors consist of the audit, political pressure, and regulation.